DESAFIOS E OPORTUNIDADES PARA A IMPLEMENTAÇÃO DE BIM E CRONOGRAMAS PARA GERENCIAMENTO DE OBRAS - Crippa, Julianna; Santos, Adriana; Scheer, Sergio; Silva, Paula (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Building Information Modeling (BIM) can be an effective instrument for planning and scheduling. Therefore, this paper aims to determine the current state of the art of BIM integrated with construction planning and control to answer the following question: Based on studies that associate BIM and scheduling tools, which are the barriers/difficulties and opportunities to apply BIM integrated with scheduling for construction management? A methodological approach was adopted in this study through a Systematic Review of Literature (RSL). This method of data collection was selected in order to define the current state of the art of the integration of BIM with planning tools, especially for scheduling. This paper presents evidences of relevant studies on this topic and it opens a discussion about the challenges, limitations and opportunities of this integration. During this research, it was verified that there is an expressive amount of studies about the use of technologies such as virtual reality (VR), radio frequency identification (RFID) and aerial photography in planning and control construction content, thus, as a suggestion for future research, the authors should develop a study aiming to understand better how the integration of these sort of technologies works with BIM.